Variable flux control of permanent magnet synchronous motor drives for constant torque operation. - Vaez-Zadeh, S. (IEEE Transactions on power electronics)
In this paper, a small signal model of permanent magnet synchronous machines is developed which includes both components of torque, i.e., magnet torque and reluctance torque. The effects of flux variations on the torque are analyzed by the use of the developed model. The off-line torque compensation method proposed for induction machines is then adapted to permanent magnet motor drives to achieve a constant torque, variable flux operation of the drives. A sensitivity analysis is performed to show that the off-line method is influenced considerably by machine parameter variations. Therefore the concept of forced compensation is introduced and an on-line torque compensation controller is proposed. Simulation results are presented to show the effectiveness of the proposed controller. An experimental vector controlled permanent magnet motor drive including the on-line torque compensation controller is implemented based on a TMS320C31 DSP to evaluate the method. The experimental results also confirm a desirable variable flux control of the motor drive under constant torque operation